REFINING THE CALCULATION OF THE CAR TRACTION POWER - E. A. Maksimov; E. P. Chelyabinsk (Вестник СибАДИ, 2019)
Introduction. Traction power of the car is used to determine its traction-speed properties. The purpose of the paper is the calculation refinement of the car traction power.Materials and methods. The authors used the methodology of the refined calculation of the car traction power.Results. The authors carried out the comparative analysis of the refined and traditional methods for calculating traction power. As a result, the authors obtained the refined equation for calculating the traction power, taking into account the elastic modulus, the width of the contact track, the free radius of the wheel, the deflection of the tire and the tangential friction forces in the contact zone. The largest discrepancy between the curve of the vehicle’s traction power calculated by the updated methodology and the curve of the vehicle’s traction power calculated by the traditional method was 26.8%.Discussion and conclusions. The results of the research are useful to specialists of automobile and transport enterprises and masters of universities to compare the traction and speed properties of the various car types.